The Effect of 4 Weeks of Continuous Exercises with Abdominal Fat Tissue Massage on Body Composition Changes in Overweight People: A Pilot Study - Moein Fasihiyan; Saber Niazi; Tahereh Hozouri; Maryam Nourshahi; Fariborz Hovanloo (Iranian Journal of Diabetes and Obesity)
Objective: This study aimed to investigate the effect of 4 weeks of continuous exercise combined with abdominal fat tissue massage on body composition in overweight individuals. Materials and Methods: Twenty-two participants (mean (±SD) age 28(±3) years; BMI 27.5 (±1.7)) were randomly divided into three groups: continuous training (CT, N= 7), continuous training with massage (CT+MA, N= 8), and massage only (MA, N= 7). The massage groups received 15-minute abdominal massages three times a week. The CT+MA group performed moderate continuous training at 50-60% VO2peak for 45 minutes after the massage. The CT group followed the same training protocol without massage. Body composition was assessed before and after the intervention, measuring fat percentage, waist to hip ratio (WHR), abdominal hip circumference, weight, and abdominal skinfold thickness. Results: The PBF, WHR, and skinfold thickness values in the abdominal area of the CT+MA group had a significant decrease compared to MA and CT groups. Conclusion: The results suggest that abdominal massage before exercise enhances lipolysis and spot fat reduction in the massage area, probably by increasing blood supply to subcutaneous fat tissue. This intervention could be a practical approach to boost lipolysis in future research.